Aspek Hukum Wakaf Sebagai Jaminan Suatu Kredit Produktif - Muhammad Fachrurrazy; Nurul Adliyah; Devi Kartikawati (MADDIKA : Journal of Islamic Family Law, 2021)
The phenomenon of unmanaged and poorly managed waqf assets has become a polemic for neglect, switching and even changing ownership in a way that is against the law. If the waqf assets are managed and productively used as collateral for productive credit, the benefits of the waqf will be in accordance with their designation. However, what often happens is that waqf assets are taken over in ways that are tyrannical and against the law. The purpose and objective of this research is to analyze the benefits of waqf assets which are used as collateral for a debt loan with the aim that these waqf assets can be productive in terms of both Islamic law and positive law. The method of this research is normative juridical with an Islamic law study approach as a study material to analyze existing regulatory norms on empirical phenomena through qualitative analysis methods. The results of this study are in terms of aspects of Islamic law in accordance with empirical phenomena (Desa Bangun Jaya and DKI Jakarta) allowing the benefits of waqf property to be productive, either transferred to something more useful or used as a guarantee for financing a business/productive activity by referring to the views of the school of thought. Maliki whose ijtihad is that waqf can be justified. If we refer to the positive legal rules that apply in Indonesia through Law Number 41 of 2004 concerning Waqf, the designation of waqf must follow the time it was pledged, it is not possible to be transferred, pledged, sold, or even given away.Fenomena aset wakaf yang tidak terurus dan tidak dikelola dengan baik menjadi polemik terlantar, beralih bahkan berpindah kepemilikan dengan cara melawan hukum. jika aset wakaf dikelola diproduktifkan baik dijadikan sebagai jaminan kredit produktif maka manfaat wakaf akan sesuai dengan peruntukannya. namun, yang banyak terjadi adalah aset wakaf diambil alih dengan cara-cara yang dzalim dan melawan hukum. maksud dan tujuan penelitian ini adalah menganalisis mengenai manfaat dari harta benda wakaf yang dijadikan sebagai jaminan suatu kredit hutang dengan tujuan supaya aset wakaf ini dapat diproduktifkan kemanfaatannya baik ditinjau dari hukum islam maupun hukum positif.metode dari penelitian ini adalah normatif yuridis dengan pendekatan kajian Hukum Islam   sebagai bahan kajian untuk mengalisis norma aturan yang ada terhadap fenomena empiris melalui metode analisis kualitatif. hasil dari penelitian ini yaitu dari segi aspek hukum islam sesuai dengan fenomena empiris (Desa Bangun Jaya dan DKI Jakarta) memungkinkan manfaat dari harta benda wakaf untuk diproduktifkan baik dialihkan ke sesuatu yang lebih bermanfaat ataupun dijadikan jaminan suatu pembiayaan usaha/kegiatan prodktif dengan merujuk pandangan mazhab maliki yang ijtihadnya bahwa wakaf dapat di istibdalkan. jika kita merujuk pada kaidah hukum positif yang berlaku di Indoensia melalui Undang-Undang nomor 41 tahun 2004  tentang Wakaf maka peruntukan wakaf harus sesuai dengan pada saat diikrarkan tidak memunkinkan untuk dialihkan, dijaminkan, dijual, bahkan dihibahkan.